Pengaruh Pemberian Pupuk Organik Cair dari Limbah Kulit Buah Pisang Lilin (Musa paradisiaca L.) terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus tricolor L. var Blitum rubrum) - Eka Aulia Diatri; Leni Marlina; Rozana Zuhri (Pendidikan Biologi STKIP YPM Bangko, 2018)
The lack of utilization of waxy banana peel waste in Merangin District is a source of environmental pollution. Wax banana peel waste has the potential as a liquid organic fertilizer. This study aims to determine the effect of giving liquid organic fertilizer from wax banana peel waste on the growth of red spinach plants and to determine the dose of liquid organic fertilizer from waxy banana peel waste which gives the best results for the growth of red spinach plants. The study used a Completely Randomized Design (CRD) of one factor, consisting of 6 treatments namely P0 (0 ml / control), P1 (10 ml), P2 (20 ml), P3 (30 ml), P4 (40 ml) and P5 (50 ml) with 4 repetitions. The parameters of this study were plant height, number of leaves, leaf surface area and root length. Data were analyzed using variance analysis and continued with Duncan test 5%. The results showed that liquid organic fertilizer of wax banana peel waste had a significant effect on the number of leaves, but did not give effect to plant height, leaf surface area and root length of red spinach. Liquid organic fertilizer of wax banana peel waste 20 ml dose gives the best results on the number of red spinach plant leaves.